The reaction of the Russian public to the decree of emperor Nicholas II on religious tolerance (April 17, 1905) - Maxim Orlov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
On April 17, 1905, Emperor Nicholas II signed a decree "On strengthening the principles of religious tolerance", which became a watershed in the history of the confessional policy of the Russian Empire. The decree did not change the fundamental principles of the Russian Empire, because the Orthodox Church still remained the "dominant" religion. There was a difference in the legal status of non-Orthodox denominations (Catholicism, Protestantism in its various variants) and "non-Believers" (Muslims, Buddhists, animists). At the same time, the decree made significant adjustments to the religious system of the empire. It was granted, albeit with some restrictions, the right to switch from one religion to another, including the right to leave the Orthodox Church. Officially registered Old Believers and sectarian communities appeared, which had previously been in a semi-legal position. All these changes took place during the 1905 revolution, when the public reacted extremely excitedly to any steps taken by the authorities. The decree "On strengthening the principles of religious tolerance" was no exception. As often happens, society was divided into those who welcomed the appearance of the decree, considering it a turn towards the rule of law, a genuine act of Christian love and tolerance. Others, on the contrary, found contradictions in it, and therefore expressed skepticism and even hostility towards the authorities about the new confessional system. At the same time, there were both conservative and liberal elements of society on the part of critics. Conservative circles reacted with distrust to the tsar's decree, believing that it opens the doors to opponents of the Orthodox Church and thereby prepares the empire for disintegration. Extreme liberals and leftist intellectuals considered the government's steps insufficient, half-hearted, demanded the complete separation of the state from the Church and the establishment of equality of all faiths